2004
DOI: 10.1111/j.1600-6143.2004.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal Administration of Molsidomine, a Molecule Releasing Nitric Oxide, Reduces Renal Ischemia-Reperfusion Injury in Rats

Abstract: Ischemia reperfusion (I-R)-induced renal damage isreduced by systemic administration of the NOdependent vasodilator molsidomine. The aim of this study was to estimate the effect of direct intrarenal molsidomine administration on renal dysfunction and inflammatory reaction after experimental I-R in rats, in order to assess only renal NO effects and to obviate its systemic hemodynamic action. Ischemia was induced by renal pedicle ligation (60 min) followed by reperfusion and contralateral nephrectomy. Molsidomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 40 publications
5
26
0
9
Order By: Relevance
“…MLS treatment (before and after DOX) ameliorated the histopathological damage caused by DOX; however, treatment with MLS before DOX injection was more effective than treatment with MLS after DOX injection, with respect to protection of tubular structures (p<0.05). Thus, our histopathological results are in agreement both with our biochemical findings and with previously published data [11,12,39,40].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…MLS treatment (before and after DOX) ameliorated the histopathological damage caused by DOX; however, treatment with MLS before DOX injection was more effective than treatment with MLS after DOX injection, with respect to protection of tubular structures (p<0.05). Thus, our histopathological results are in agreement both with our biochemical findings and with previously published data [11,12,39,40].…”
Section: Discussionsupporting
confidence: 83%
“…We focused especially on the antioxidant properties of MLS, rather than the anti-inflammatory effects [9,11]. The analysis of kidney histology used a semiquantitative (vs. quantitative) method involving grading of the anti-inflammatory effects of MLS (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] Organs subjected to IRI demonstrate suppression of NO, 11 and therapies that supplement NO have been shown to mitigate IRI. [12][13][14][15] In this study, we tested the hypothesis that renal tissue-expressed CD47 promotes IRI. We demonstrate for the first time that TSP1 and CD47 are significantly induced in IRI.…”
mentioning
confidence: 99%
“…They suggested that the beneficial effects of MOL may be due to the decreasing of neutrophil infiltration. Rodriguez-Pena et al showed MOL reduced plasma levels of pro-inflammatory cytokines however it increases the levels of antiinflammatory cytokines in rats [26]. Taking into consideration the reduced oxidative damage caused by MOL treatment, all investigators attributed the protective actions of MOL to its antioxidative and anti-inflammatory activities [27].…”
Section: Discussionmentioning
confidence: 99%